Persepsi Pengunjung mengenai Aksesibilitas dan Kepuasan Wisata Kuliner Mie Aceh Titi Bobrok, Kota Medan - Azzahra, Fatimah; Azis, T. Abdillah; Durubanua, Derita Ramai; Azzarah, Regita Asiah; Sugiharto, Sugiharto; permana, Sendi; Sintong, Mahara (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze visitor satisfaction regarding the accessibility of culinary tourism at Mie Aceh Titi Bobrok in Medan Sunggal, Medan City. The method employed is qualitative descriptive. The results indicate that the majority of visitors are satisfied with the accessibility to the location, in terms of road quality, travel time, and availability of transportation. However, several challenges remain, such as traffic congestion during peak hours and limited parking facilities. The conclusion of this study emphasizes the importance of maintaining and improving accessibility quality to ensure visitor comfort and satisfaction.